QSAR Investigation on 3,5-diaryl-4,5-dihydro-1H-pyrazole-1-carbothioamides as EGFR Kinase Inhibitors - Sanmati K. Jain; Sanjay K. Lanjhiyana; Ajay Gupta; B. G. V. S. Jagan; Sunil Sahu (Challenges and Advances in Pharmaceutical Research Vol. 2, 2022)
Quantitative structure activity relationship (QSAR) study was performed on a series of 3,5-diaryl-4,5-dihydro-1H-pyrazole-1-carbothioamides in order to establish quantitative relationship between epidermal growth factor receptor (EGFR) kinase inhibitory activity and physicochemical / structural properties. Several statistical regression equations were obtained using multiple linear regression (MLR) analysis. Most statistical significant model generated (Model 2), justifies 72% (r2 = 0.7194) of the overall variance in the training set as well as it has internal (q2) and external (pred_r2) predicative ability of 65% (q2 = 0.6472) and 75% (pred_r2 = 0.7530) respectively. This model is further validated and Mean Absolute Error (MAE)-based criteria applied on 95% data showed that MAE+3* Standard Deviation (SD)[= 0.3359 < (0.25 * TrainingSetRange = 0.55250)], indicate that projection quality of the model is good. In this model positive coefficient value of T_C_C_4 [This is the count of number of carbon atoms separated from any carbon atom (single, double or triple bonded) by 4 bond distance in a molecule] and Most+ve&-ve Potentail Distance [This descriptor signifies the distance between points having the highest value of +ve and highest value of –ve electrostatic potential on van der waals surface area of the molecule] on the biological activity indicated that higher value leads to enhanced epidermal growth factor receptor (EGFR) kinase inhibitory activity whereas lower value leads to decrease activity. Contribution chart reveals that the descriptors T_C_C_4 and Most+ve&-ve Potentail Distance contributing 75.97% and 24.03% respectively.